1985
DOI: 10.1002/jbm.820190105
|View full text |Cite
|
Sign up to set email alerts
|

In situ replication techniques: II. Quantitative methodologies for replicate materials

Abstract: Because replicate materials have requirements different from those of recording or impression materials, quantitative methodologies were sought using commercial impression materials. Two satisfactory objective techniques resulted, a laser-scattering and a capillary flow test. Using high-resolution gratings to stimulate tooth detail (less than 1 micron), the reproduction quality of 36 two-stage replicas was determined in diffraction, reflection, and in an unblazed state. Using precision bore glass tubes (0.25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A method designed to test the accuracy of various impression materials when used for this procedure showed the addition-cured silicone materials to be the most accurate (Kusy & Whitley, 1985) although other workers have recommended the use of condensationcured silicone material (Hirt, Lutz & Roulet, 1984). A recent systematic inquiry into the use of high-resolution replica materials concluded that a standardization of technique would allow researchers to directly compare studies (Bromage, 1985).…”
Section: Critical Evaluations Using the Scanning Electron Microscopementioning
confidence: 99%
“…A method designed to test the accuracy of various impression materials when used for this procedure showed the addition-cured silicone materials to be the most accurate (Kusy & Whitley, 1985) although other workers have recommended the use of condensationcured silicone material (Hirt, Lutz & Roulet, 1984). A recent systematic inquiry into the use of high-resolution replica materials concluded that a standardization of technique would allow researchers to directly compare studies (Bromage, 1985).…”
Section: Critical Evaluations Using the Scanning Electron Microscopementioning
confidence: 99%